Analysis of the accessibility in websites of Ecuadorian universities of excellence - Acosta, Tania; Luján-Mora, Sergio (Enfoque UTE, 2017)
Since the publication of the Ecuadorian Technical Standard NTE INEN ISO / IEC 40500 in 2014 and the Ecuadorian Technical Regulation RTE INEN 288 "The web contents accessibility" in 2016, web accessibility in Ecuador has taken great importance. In the educational field, the websites of Higher Education Institutions (HEI) have become a communication channel, where universities publish the information and services they offer. In addition, HEI must satisfy the rights of all citizens to have access to education, which includes persons with disabilities. In order to ensure access to the websites of HEI to all people it is important that HEI incorporate web accessibility as an essential requirement in their websites. The objective of this research is to perform the accessibility analysis of the websites of the Ecuadorian universities of excellence belonging to categories A, B and C; identify websites accessibility errors and to present some recommendations for a better fulfillment of the WCAG 2.0 accessibility guidelines by website designers and developers.